Pemasaran Hubungan Dan Optimalisasi Peran Manajer Menengah Dalam Perencanaan Dan Strategi Pemasaran - Albari Albari (Jurnal Aplikasi Bisnis, 2017)
Preparation ofplanning andmarketing strategy development is an activity that must be done by marketing management in accordance with the duties and responsibilities. But in its development, these activities are often not run as expected, both of the process and implementation. This article provides a discourse that is needed in terms of planning and marketing strategies, particularly with regard to relationship marketing materials and optimizing the role of middle managers. To provide more complete understanding of this description, it also includes discussion of important aspects, such as the relationship with environmental analysis, internal and external marketing and performance evaluation.